Automated health monitoring and watering system for plants (plant nursing system) - Bin Mostafiz, Rahatil; Fuad, Muhtasim; Sarker, Hasan Sakib; Ahmed, Mushfique (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.